The Influence of Interpersonal Communication of School Principals and Academic Supervision of School Supervisors on the Performance of Junior High School Teachers in Parlilitan District, Humbang Hasundutan Regency - Simanullang, Marlenni; Samosir, Lustani; Saragih, Ratna; Sitopu, Elisamark; Simanullang, Pardomuan (Journal of Educational Analytics, 2024)
This study aims to determine the effect of interpersonal communication and academic supervision of school supervisors on teacher performance partially and simultaneously. This study uses a descriptive quantitative method. The population of the study was all junior high school teachers in Parlilitan District, totaling 104 people with a sample of 104 people. The questionnaire trial was conducted on 30 teachers outside the research sample, and has been tested with validity and reliability tests. The data analysis technique used multiple linear regression tests. The results of the study showed: 1). There is an effect of interpersonal communication on teacher performance of 48.9%, with rx1y of 0.671 in a positive direction, in a strong interpretation. 2). There is a positive effect of interpersonal communication and academic supervision of school supervisors simultaneously on teacher performance of 56.6%, the multiple correlation coefficient of R = 0.752 is in a strong interpretation, thus H0 is rejected and Ha is accepted, meaning that there is a positive effect between interpersonal communication and academic supervision of school supervisors on the performance of junior high school teachers in Parlilitan District partially and simultaneously because it has been tested empirically. The results of this study recommend to related elements that in order to improve teacher performance, interpersonal communication between school principals and academic supervision .